CONFLICTS OF GESTURES, CONFLICTS OF IMAGES - Didi-Huberman, Georges (The Nordic Journal of Aesthetics, 2018)
The article presents some notes for an anthropology of the gestures of uprising [soulèvement]. It argues that, just as sounds (screams, words, slogans) always come out of the mouth of the demonstra- tors, images of all kinds are also brandished at the end of their arms. Based on this the article raises the question of the very notion of a desire for uprising.